1995
DOI: 10.1002/ajim.4700270108
|View full text |Cite
|
Sign up to set email alerts
|

Relations between upper limb soft tissue disorders and repetitive movements at work

Abstract: To make a preliminary assessment of whether upper limb soft tissue disorders might be associated with activities at work, we have conducted a case-control study of subjects attending orthopedic clinics in three cities. All subjects between the ages of 16 and 65 years, in whom defined soft tissue conditions of the upper limb were diagnosed by the participating orthopedic surgeons, were invited to take part. Controls were subjects attending the same clinics within the same age range whose clinical diagnosis did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 11 publications
0
49
0
4
Order By: Relevance
“…The one-time injury that we created with the surgical procedure might be another limitation, as it is widely accepted (although experimental data are limited) that forceful and repetitive finger movements contribute to the development of CTS [1,2]. However, our injury was designed so that the advancement of the FDS3 would stretch its surrounding SSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The one-time injury that we created with the surgical procedure might be another limitation, as it is widely accepted (although experimental data are limited) that forceful and repetitive finger movements contribute to the development of CTS [1,2]. However, our injury was designed so that the advancement of the FDS3 would stretch its surrounding SSCT.…”
Section: Discussionmentioning
confidence: 99%
“…They found that subjects with upper extremity disorders were more likely to perform certain occupations (for example, hairdressers, assembly line workers, machine operators, and electricians). 24 However, logistic regression analysis found negative association between CTS and wrist ergonomic factors (OR ϭ 0.39). The study conducted by Werner et al 25 found that the workers who complained of hand symptoms were more likely to have ergonomic risk factors compared with asymptomatic workers who had similar NCV findings (P ϭ .002).…”
Section: Epidemiological Studies Set the Stagementioning
confidence: 97%
“…23 Studies published in recent years have continued to report divergent results. English et al (1995) studied 580 patients attending an orthopedic clinic and matched them with 996 control subjects. They found that subjects with upper extremity disorders were more likely to perform certain occupations (for example, hairdressers, assembly line workers, machine operators, and electricians).…”
Section: Epidemiological Studies Set the Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Apesar dos critérios bem definidos de coleta e diagnóstico, a amostra do estudo foi pequena (79 trabalhadoras expostas). English et al (1995), em um estudo exploratório do tipo caso-controle, encontraram associação entre lesões de membros superiores e movimentos específicos realizados em diferentes atividades de trabalho. Os casos e controles foram selecionados em clínicas ortopédicas, sendo o diagnóstico mais freqüente entre os casos a síndrome do túnel do carpo.…”
Section: Introductionunclassified